Notorious New Jersey: 100 true tales of murders and mobsters, scandals and scoundrels - Blackwell, Jon (Rivergate Books, 2008)
Acknowledgments -- Introduction -- Old rascals : crime and infamy before 1900 -- Dead wrong : notorious murders -- Mob paradise : the Jersey underworld -- Power corruption : politicians and other crooks -- Enemy action : terrorists, radicals, spies, and invaders -- Causes celebres : controversies and whodunits -- Bibliography -- Index